Cutaneous manifestations of SARS‐CoV‐2 infection during the Delta and Omicron waves in 348 691 UK users of the UK ZOE COVID Study app. (10th October 2022) - Visconti, Alessia; Murray, Benjamin; Rossi, Niccolò; Wolf, Jonathan; Ourselin, Sebastien; Spector, Tim D.; Freeman, Esther E.; Bataille, Veronique; Falchi, Mario
Summary: Background: Symptoms of SARS‐CoV‐2 infection have differed during the different waves of the pandemic but little is known about how cutaneous manifestations have changed. Objectives: To investigate the diagnostic value, frequency and duration of cutaneous manifestations of SARS‐CoV‐2 infection and to explore their variations between the Delta and Omicron waves of the pandemic. Methods: In this retrospective study, we used self‐reported data from 348 691 UK users of the ZOE COVID Study app, matched 1 : 1 for age, sex, vaccination status and self‐reported eczema diagnosis between the Delta and Omicron waves, to assess the diagnostic value, frequency and duration of five cutaneous manifestations of SARS‐CoV‐2 infection (acral, burning, erythematopapular and urticarial rash, and unusual hair loss), and how these changed between waves. We also investigated whether vaccination had any effect on symptom frequency. Results: We show a significant association between any cutaneous manifestations and a positive SARS‐CoV‐2 test result, with a diagnostic value higher in the Delta compared with the Omicron wave (odds ratio 2·29, 95% confidence interval 2·22–2·36, P  < 0·001; and odds ratio 1·29, 95% confidence interval 1·26–1·33, P  < 0·001, respectively). Cutaneous manifestations were also more common with Delta vs. Omicron (17·6% vs. 11·4%, respectively) and had a longer duration. During both waves, cutaneous symptoms clustered with other frequent symptoms and rarely (in < 2% of the users) as first or only clinical sign of SARS‐CoV‐2 infection. Finally, we observed that vaccinated and unvaccinated users showed similar odds of presenting with a cutaneous manifestation, apart from burning rash, where the odds were lower in vaccinated users. Conclusions: Cutaneous manifestations are predictive of SARS‐CoV‐2 infection, and their frequency and duration have changed with different variants. Therefore, we advocate for their inclusion in the list of clinically relevant COVID‐19 symptoms and suggest that their monitoring could help identify new variants. What is already known about this topic? Several studies during the wildtype COVID‐19 wave reported that patients presented with common skin‐related symptoms. It has been observed that COVID‐19 symptoms differ among variants. No study has focused on how skin‐related symptoms have changed across different variants. What does this study add? We showed, in a community‐based retrospective study including over 348 000 individuals, that the presence of cutaneous symptoms is predictive of SARS‐CoV‐2 infection during the Delta and Omicron waves and that this diagnostic value, along with symptom frequency and duration, differs between variants. We showed that infected vaccinated and unvaccinated individuals reported similar skin‐related symptoms during the Delta and Omicron waves, with only burning rashes being less common after vaccination. Abstract : Odds ratios in adults testing positive for COVID‐19 of self‐reporting some of the typical COVID‐19 symptoms and skin signs of COVID‐19 infection. Results are based on 198 609 users of the ZOE COVID Study App that self‐reported their symptoms during the Delta wave and 198 609 users matched for age, sex, vaccination status and self‐reported eczema diagnosis that self‐reported their symptoms during the Omicron wave. The OR for anosmia (13·4, 95% confidence interval 13·1–13·8) is not shown for the Delta wave to improve visualization. Linked Comment: M. Grau‐Pérez and I. Garcia‐Doval. Br J Dermatol 2022; 187:839 . Plain language summary available online